Clinical methods in medicine clinical skills and practices - Chugh, S. N.; Gupta, Eshan (Jaypee The Health Sciences Publishers, 2015)
Fully revised second edition presenting latest advances in clinical examination techniques. Covers both physical and systemic examination methods. More than 1250 clinical photographs, diagrams and tables. Previous edition published in 2009.